2017
DOI: 10.1016/j.jff.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and major phenol compounds of horticultural plant materials not usually used

Abstract: HighlightsAntioxidant properties and phenols in plant materials not usually used were studied.Folin-Ciocalteu, FRAP and ABTS measures correlate with different phenol compounds.Large differences in antioxidant properties were found between and within species.Sea buckthorn and black currant leaves had the highest antioxidant capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 16 publications
4
43
0
1
Order By: Relevance
“…Comparable outcomes of phenolic compounds were obtained by [16], and high contents in this present study were slightly lower than those reported in the literature. is discrepancy may be due to the existence of various amounts of sugars, ascorbic acid or carotenoids or the duration, extraction strategies, or geographical variation, which might also regulate the formation of phenolic aggregates [33]. As reported in a previous study, compared with other plant species, jute leaves have much higher amounts of total polyphenol contents in Paederia foetida leaves containing 4.96 mg GAE/g [34], and 109.21-116.70 mg/100 g in sorghum [35].…”
Section: Total Polyphenol Content (Tpc)mentioning
confidence: 99%
“…Comparable outcomes of phenolic compounds were obtained by [16], and high contents in this present study were slightly lower than those reported in the literature. is discrepancy may be due to the existence of various amounts of sugars, ascorbic acid or carotenoids or the duration, extraction strategies, or geographical variation, which might also regulate the formation of phenolic aggregates [33]. As reported in a previous study, compared with other plant species, jute leaves have much higher amounts of total polyphenol contents in Paederia foetida leaves containing 4.96 mg GAE/g [34], and 109.21-116.70 mg/100 g in sorghum [35].…”
Section: Total Polyphenol Content (Tpc)mentioning
confidence: 99%
“…Resveratrol, a natural polyphenolic, non-flavonoid antioxidant (trans-3, 40, 5-trihydroxystylben), is a phytoalexin which has high levels of food products, especially red wine made from grapes (Sayin et al 2017). The antioxidant properties of plant extracts containing phenol group have been shown in previous studies (Burri et al 2017;Zhang et al 2018). Resveratrol has important anti-inflammatory, antioxidant and immunomodulatory properties (Soufi et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Phenolic compounds such as gallic acid, catechin, and epicatechin are notoriously endowed with antioxidants, astringents, and antimicrobial activity. Therefore, such species are subject of increasing interest in various fields such as pharmaceuticals, leather tanning, cosmetics, and the food industry [7][8][9][10][11]. Low-molecular-weight hydroxybenzoic acids and some of their derivatives can be obtained from wood extractives and via induced lignin degradation [12,13].…”
Section: Introductionmentioning
confidence: 99%